DIMENSIONS OF AGRICULTURAL MODERNIZATION: A MULTIVARIATE APPROACH TO TECHNOLOGICAL LEVELS IN RONDÔNIA, BRAZILIAN AMAZON - Silva, Shirlei dos Santos; Mota, Vania Corrêa; Cordeiro, Kíssia Alana Silva; Sakuno, Irene Yoko Taguchi (Seven Editora, 2026)
This study aimed to characterize rural establishments in the state of Rondônia based on records from the 2017 Agricultural Census, using multivariate statistical analysis methods to determine the municipal technological level based on factor scores. The methodological foundation consisted of applying Factor Analysis and Cluster Analysis techniques. Six latent factors were identified—named Plantation, Soil, Technical Instruction, Livestock, Dairy Production, and Rural Modernization—which, together, explained 82.5% of the total variability of the analyzed data. The cluster analysis, validated by K-means and hierarchical methods, revealed that the division into two distinct groups adequately represents the productive heterogeneity of the state. Regarding the technological level (ITEA), it was found that the municipalities are distributed only between the medium and low categories, with no localities at extreme levels (high or very low). The municipality of Pimenteiras do Oeste obtained the highest technological index, standing out as a reference for agricultural modernization in the region. It is concluded that multivariate modeling is a robust and suitable tool to support regional diagnoses and guide public policies aimed at sustainable rural development in Rondônia.